Heat transfer in fuel oil storage tank at thermal power plants with local fuel heating; MATEC Web of Conferences; Vol. 23 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment - Kuznetsova S. A. Svetlana (2015, 2015)
Title screen